Collective action and property rights for sustainable rangeland management - Mwangi, Esther (CGIAR, 2005)
The research had the following objectives: • To better understand how environmental risk affects the use and management of resources under various property rights regimes • To identify circumstances under which different pathways of change in land use and property rights are followed • To identify how policy and other external interventions can help communities achieve desirable pathways and mitigate negative impacts of undesirable pathways